PENGEMBANGAN BAHAN AJAR BUKU SAKU BERBASIS PEMBELAJARAN KONTEKSTUAL KELAS V SDN 14 PONTIANAK SELATAN - Srikandi Srikandi; Kartono Kartono; Suhardi Marli (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2020)
AbstractThis research aims to produce a teaching product in a contextual learning pocketbook. This is kind of development research, which refers to a research model developed by the borg and gall.The subject of this study is a class V of elementary school 14 in south pontianak. The instruments used to collect data on these studies are interview manuals, observation manuals and angkets.This step of research is information gathering and research, planning, development of pre-defined forms of product, validation, revision, individual trials and small group trials.A context-based manual product that was developed is validated by materials and design experts prior to testing for learners.Studies show that the results of the validation of materials experts have scored an average of 3.705, which is an excellent category and that designers have scored a 3.66 average score.Based on individual trials, the individuals scored an average of 3.20 in good category, and based on trials of small groups, scored an average of 3.41 in high category.Based on research results, it may be concluded that a pocketbook based in contextual study of a class V of elementary school number 14 in south pontianak iis worthy of use for all levels of educational ability.Keyword: contextual, development, teaching materials